Biomechanical consequences of branching in flexible wave‐swept macroalgae. Issue 1 (20th November 2014) - Starko, Samuel; Claman, Barry Z.; Martone, Patrick T.
Summary Wave‐swept macroalgae present an excellent system for studying the effects of chronic physical stress on the morphological evolution of plants. Wave‐induced water velocities impose great drag forces, leading to a morphological tradeoff between light interception and drag reduction/tolerance. What are the hydrodynamic consequences of morphological diversification, such as increased branching? Drag was measured on artificial macroalgae of constant 'photosynthetic' area, but differing branching patterns, in a high‐speed flume at water velocities up to 3.5 m s−1. A meta‐analysis was used to compare dislodgement forces of branched and unbranched species of comparable sizes in the field to determine if drag‐prone morphologies had greater attachment strengths. Branched fronds experienced greater drag than unbranched fronds of the same size. Greater drag in branched forms was not the result of increased projected area but probably resulted from greater pressure or friction drag. In the field, branched species resisted greater dislodgement forces than unbranched species of comparable size, suggesting that branched species compensate for increased drag with stronger attachment to the substratum. Branching has clear biomechanical consequences, increasing drag and the need for increased attachment. This raises questions about physiological and ecological advantages that may have driven the repeated evolution of biomechanically costly, branched morphologies.